Contesting Corporal Punishment: Abolitionism, Transportation and the British Imperial Project - Barrett Meyering, Isobelle (2008)
Between the 1820s and the 1840s, anti-slavery ideas shaped debate about the treatment of convicts in the Australian penal colonies. This thesis investigates the impact of abolitionism on one key aspect of convict life: the use of corporal punishment. It traces the rise and decline of abolitionist rhetoric in the work of three vocal critics of flogging: newspaper editor Edward Smith Hall (1786-1860); English politician William Molesworth (1810-1855); and penal reformer Captain Alexander Maconochie (1787-1860). It highlights the connections between their opposition to flogging and their anxieties about the legitimacy of the wider British imperial project